Membrane phospholipid asymmetry as a determinant of erythrocyte recognition by macrophages. - McEvoy, L (1986)
To assess the role of transbilayer phospholipid distribution in the recognition and phagocytosis of erythrocytes by macrophages, human erythrocytes with either a symmetric or asymmetric distribution of membrane phospholipids were prepared by hypotonic hemolysis and then incubated with cultures of human monocyte-derived macrophages. Erythrocytes with an abnormal, symmetric distribution were phagocytosed 4 times more readily than their counterparts with an asymmetric distribution or than normal, asymmetric intact erythrocytes. This enhanced phagocytosis correlated with two biophysical properties of the membrane: the spacing of phospholipids, as assessed by binding of the dye merocyanine 540, and the relative hydrophobicity, as measured by aqueous two-phase polymer partitioning. These results suggest a mechanism by which loss of membrane asymmetry is translated into recognition by macrophages and provide guidelines in loading erythrocytes that may be useful in manipulating the mode of delivery when erythrocytes are used as drug carriers in vivo.